Seasonal and geographic variations in the incidence of asthma exacerbations in the United States. (14th September 2017) - Gerhardsson de Verdier, M.; Gustafson, Per; McCrae, Christopher; Edsbäcker, Staffan; Johnston, Neil
ABSTRACT: Background : Exacerbations drive the burden of asthma and lead to significant morbidity and consumption of health care resources. Many prior studies of the epidemiology of asthma exacerbations have relied upon data from hospital care. Objective : The objective of this study was to determine US patterns of geographic and seasonal variations of asthma exacerbations being defined as asthma episodes requiring hospital care and/or a prescription for oral steroid. Methods : The study was a retrospective observational cohort study using administrative claims data for insured individuals from the HealthCore Integrated Research Database, including around 43 million members in the United States. Analyses examined 3 age groups, 6–17, 18–64, and ≥65 years and four US regions, Northeast, Southeast, Central, and Western. Results : Monthly rates of asthma exacerbations showed the greatest variation over the year in children, less so in adults and in the elderly. Clinically important differences in rates of asthma exacerbation were observed between regions with the Western Region having the lowest in all three age groups followed by the Northeast, Central, and Southeast regions. Peaks in children occurred in the early fall following troughs in the summer months, and peaks at year-end occurred in adults, particularly in those over 65 years. Conclusions : There is a striking seasonal variation in asthma exacerbations in the United States. Substantial differences between regions of the United States in asthma exacerbation rates cannot readily be explained and invite further investigation.